Effect of planting spaces and fertilization package on the productivity and prolific level of maize var. Sinhas 1. Issue 4 (July 2021) - Farid, Muh.; Padjung, Rusnadi; Nasaruddin,; Ridwan, I
Abstract: A study aimed to determine planting system and fertilization packages that give the best result on productivity and prolific level of Maize was conducted. Maize variety Sinhas 1 was planted with three planting systems to design different planting spaces between and within the rows. A Legowo planting system was used with two models, ie. Legowo (50+100) × 20 cm and Legowo (50+100) × 18 cm, resulted in a total of 66, 667 and 74, 074 population per hectare, respectively. A normal planting spacing of 75 × 20 cm was used as control with a total population of 66, 667 plants per hectare. Four fertilization packages were used consisted of N:P:K= 225:100:75; N:P:K= 200:100:60 + KNO3 10 kg; N:P:K= 225:100:75 + Ecofarming 5cc/L; and N:P:K= 200:100:50 + KNO3 10 kg + Ecofarming 5 cc/L. A split plot experimental design was employed. Results show that Legowo planting system and fertilization packages significantly increased the productivity and the prolific level of the maize. Planting density of Legowo (50+100) × 20 cm applied with N:P:K = 200:100:50 + KNO3 10 kg + Ecofarming 5cc/L resulted in the highest productivity of 10.43 t ha −1 with percentage of prolific of 73.36%.